The physicochemical, functional, and pasting properties of Moringa oleifera leaf powder from different leaf stalk colors - Ambar Fidyasari; Teti Estiasih; Siti Narsito Wulan; Alfi Khatib (CyTA - Journal of Food)
Moringa oleifera (MO) leaf powder (MOLP) is functional, and its composition affects its use. The MO tree has different colors i.e. white, green, and red. This study aimed to evaluate MOLP physicochemical, functional, and pasting properties based on the leaf stalk color as the basis for their suitable use in food products. Leaf stalk color slightly affect characteristics, with typical high protein, dietary fiber, and ash, but low starch and fat. MOLP has high soluble dietary fiber, high amylose starch, and significant amounts of phenolics and flavonoids. Chlorophyll is the abundant pigment followed by β carotene. MOLP is rich in essential amino acids with methionine is a limiting essential amino acid. MOLP has almost equal saturated and unsaturated, and rich in essential fatty acids. Low starch and high fiber affect pasting properties, exhibiting low viscosity and gelatinization temperature, but high stability. Low solubility of MOLP is a challenge to improve.